The Effectiveness of Pregnant Women's Class on the Success of Exclusive Breastfeeding - Indrawati Aris Tyarini; Yoga Tri Wijayanti; Asridawati Akib; Nofita Tudang Rombeallo; Sitti Zakiyyah Putri (Jurnal Ilmiah Kesehatan Sandi Husada)
Introduction: Exclusive breastfeeding (EBF) during the first six months of life plays a crucial role in infant survival, growth, and development. However, the global rates of EBF remain below the recommended targets. Pregnant women's classes are designed to provide education, support, and skills necessary for successful breastfeeding practices. This study aimed to analyze the effectiveness of pregnant women's classes on the success rate of exclusive breastfeeding.